Effective gene therapy for metachromatic leukodystrophy achieved with minimal lentiviral genomic integrations - Lucas Tricoli; Sunetra Sase; Julia L. Hacker; Vi Pham; Maxwell Chappell; Laura Breda; Stephanie N. Hurwitz; Naoto Tanaka; Carlo Castruccio Castracani; Amaliris Guerra; Zhongqi Hou; Lars Schlotawa; et al. (Molecular Therapy: Nucleic Acids)
Metachromatic leukodystrophy (MLD) is a fatal lysosomal storage disease characterized by the deficient enzymatic activity of arylsulfatase A (ARSA). Combined autologous hematopoietic stem cell transplantion (HSCT) with lentiviral (LV)-based gene therapy has great potential to treat MLD. Achieving the optimal balance between high enzyme production for therapeutic efficacy and maintaining a low vector copy number (VCN) is crucial. Insufficient enzyme levels can lead to the progression of motor symptoms, undermining treatment goals. Conversely, elevated VCN increases the risk of genotoxicity, which poses safety concerns, and contributes to higher production costs, making the therapy less accessible. Striking this balance is essential to maximize clinical benefit while minimizing risks and costs. To address this need, we increased the expression of ARSA cDNA at single integration by generating novel LVs, optimizing ARSA expression and enhancing safety. In addition, our vectors achieved optimal transduction in mouse and human hematopoietic stem cells (HSCs) with minimal multiplicity of infection (MOI). Our top-performing vector (EA1) showed at least 4× more ARSA activity than the currently US and European Union (EU)-approved vector and a superior ability to secrete vesicle-associated ARSA, a critical modality to transfer functional enzymes from microglia to oligodendrocytes. Three-month-old Arsa-knockout (KO) MLD mice transplanted with Arsa-KO bone marrow (BM) cells transduced with 0.6 VCN of EA1 demonstrated behavior and CNS histology matching wild-type (WT) mice. Our novel vector boosts efficacy while improving safety as a robust approach for treating MLD patients.